1997
DOI: 10.1073/pnas.94.11.5628
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA deadenylylation precedes decapping in mammalian cells

Abstract: In yeast, the major mRNA degradation pathway is initiated by poly(A) tail shortening that triggers mRNA decapping. The mRNA is then degraded by 5-to-3 exonucleolysis. In mammalian cells, even though poly(A) tail shortening also precedes mRNA degradation, the degradation pathway has not been elucidated. We have used a reverse transcription-PCR approach that relies on mRNA circularization to measure the poly(A) tail length of four mammalian mRNAs. This approach allows for the simultaneous analysis of the 5 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
191
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(194 citation statements)
references
References 46 publications
(54 reference statements)
2
191
1
Order By: Relevance
“…The poly(A) tail is added in the nucleus during the process of pre-mRNA 39 end formation, which consists of endonucleolytic cleavage followed by polyadenylation of the upstream fragment (Proudfoot, 1996;Colgan & Manley, 1997)+ The length of the poly(A) tail appears to be controlled by regulating the activity of the poly(A) polymerase+ The poly(A) binding proteins, Pab I (in yeast) and Pab II (in mammals), are thought to be involved in this process+ In yeast, cellular extracts from strains mutated or deleted for the PAB1 gene generate abnormally long poly(A) tails (Amrani et al+, 1997;Minvielle-Sebastia et al+, 1997)+ However, in mammalian cells, Pab1 seems to accumulate only in the cytoplasm+ Here, it is Pab II that is involved in regulating the length of the poly(A) tail, and it does this by stimulating the elongation of a shorter poly(A) tail (Wahle, 1995)+ In Drosophila, we do not yet know if Pab1 or Pab2 are involved in regulating the length of the nuclear poly(A) tail+ However, considering the phenotype of PAB1 mutations in yeast, one could interpret the data in this paper as an indication that in Drosophila (at least for the Adh gene), similar to yeast, the relative short length of the poly(A) tail of the wild-type Adh transcript may be achieved by preventing its elongation to a "default" longer tail+ The presence of a premature termination codon appears to affect this process and lead to longer poly(A) tails+ Therefore, it seems to be a reasonable suggestion that there may be a link between the nuclear process of pre-mRNA 39 end processing and scanning of the coding region+ However, more work is required to establish if there are direct effects on the machinery that generates the 39 end of the mRNA or if the poly(A) extension is a secondary consequence of interference with other steps during pre-mRNA processing+ For example, at this stage it cannot be excluded that the elongation of the poly(A) could just be a secondary consequence of a delay in splicing or/and trafficking+ However, these data also raise the question of whether there is a causal link between abnormal 39 processing and reduction in the mRNA levels+ The increase in length of the poly(A) tail is not expected to trigger mRNA decay+ This is supported by several studies in yeast and mammals indicating that actually poly(A) shortening precedes mRNA degradation (Decker & Parker, 1994;Beelman & Parker, 1995;Couttet et al+, 1997)+ It has FIGURE 8. The Adh pre-mRNA is longer in nonsense mutants+ Northern blot analysis of total RNA (5-10 mg)+ The RNA was fractionated overnight on a 1+2% agarose formaldehyde gel; formaldehyde was also added to the buffer+ The filter was first hybridized with a probe specific for the first Adh intron, then stripped and probed with a probe specific for RpL3 (see Fig+ 2)+ The intron specific probe was PCR amplified from a genomic clone with two primers at positions 1392 and 1777 relative to the sequence X78384 (see Fig+ 1A)+ Note that the lane with wild-type RNA contains more RNA than the others+ been shown that in yeast, however, premature translational termination can trigger mRNA degradation independently of deadenylation (Muhlrad & Parker, 1994)+ Evidently it would still be interesting to check the stability of these nonsense mRNAs+ Unfortunately, it has been difficult so far to est...…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The poly(A) tail is added in the nucleus during the process of pre-mRNA 39 end formation, which consists of endonucleolytic cleavage followed by polyadenylation of the upstream fragment (Proudfoot, 1996;Colgan & Manley, 1997)+ The length of the poly(A) tail appears to be controlled by regulating the activity of the poly(A) polymerase+ The poly(A) binding proteins, Pab I (in yeast) and Pab II (in mammals), are thought to be involved in this process+ In yeast, cellular extracts from strains mutated or deleted for the PAB1 gene generate abnormally long poly(A) tails (Amrani et al+, 1997;Minvielle-Sebastia et al+, 1997)+ However, in mammalian cells, Pab1 seems to accumulate only in the cytoplasm+ Here, it is Pab II that is involved in regulating the length of the poly(A) tail, and it does this by stimulating the elongation of a shorter poly(A) tail (Wahle, 1995)+ In Drosophila, we do not yet know if Pab1 or Pab2 are involved in regulating the length of the nuclear poly(A) tail+ However, considering the phenotype of PAB1 mutations in yeast, one could interpret the data in this paper as an indication that in Drosophila (at least for the Adh gene), similar to yeast, the relative short length of the poly(A) tail of the wild-type Adh transcript may be achieved by preventing its elongation to a "default" longer tail+ The presence of a premature termination codon appears to affect this process and lead to longer poly(A) tails+ Therefore, it seems to be a reasonable suggestion that there may be a link between the nuclear process of pre-mRNA 39 end processing and scanning of the coding region+ However, more work is required to establish if there are direct effects on the machinery that generates the 39 end of the mRNA or if the poly(A) extension is a secondary consequence of interference with other steps during pre-mRNA processing+ For example, at this stage it cannot be excluded that the elongation of the poly(A) could just be a secondary consequence of a delay in splicing or/and trafficking+ However, these data also raise the question of whether there is a causal link between abnormal 39 processing and reduction in the mRNA levels+ The increase in length of the poly(A) tail is not expected to trigger mRNA decay+ This is supported by several studies in yeast and mammals indicating that actually poly(A) shortening precedes mRNA degradation (Decker & Parker, 1994;Beelman & Parker, 1995;Couttet et al+, 1997)+ It has FIGURE 8. The Adh pre-mRNA is longer in nonsense mutants+ Northern blot analysis of total RNA (5-10 mg)+ The RNA was fractionated overnight on a 1+2% agarose formaldehyde gel; formaldehyde was also added to the buffer+ The filter was first hybridized with a probe specific for the first Adh intron, then stripped and probed with a probe specific for RpL3 (see Fig+ 2)+ The intron specific probe was PCR amplified from a genomic clone with two primers at positions 1392 and 1777 relative to the sequence X78384 (see Fig+ 1A)+ Note that the lane with wild-type RNA contains more RNA than the others+ been shown that in yeast, however, premature translational termination can trigger mRNA degradation independently of deadenylation (Muhlrad & Parker, 1994)+ Evidently it would still be interesting to check the stability of these nonsense mRNAs+ Unfortunately, it has been difficult so far to est...…”
Section: Discussionmentioning
confidence: 96%
“…To gain more detailed information on the effect of nonsense mutations on the length of the poly(A) tail, I followed an alternative experimental approach that makes use of the sensitivity of PCR+ The basic principle of this technique is the circularization of in vitro decapped RNA followed by cDNA synthesis across the junction and subsequent PCR with primers hybridizing to the flanking sequences (Couttet et al+, 1997; a schematic diagram of this technique is shown in Fig+ 5A)+ This technique can be applied to determine precisely the length of the poly(A) tails and identify other potential changes in 59 and 39 ends of the Adh transcripts (see Materials and Methods)+ Circularized RNA was prepared and cDNA synthesized using a primer complementary to the beginning of exon 2 (Fig+ 1, primer E)+ Two rounds of PCR were performed, the first with primers G and D and the subsequent one with the two nested primers A and H (Fig+ 1B shows the position of the primers)+ Two parallel experiments were performed+ In one of them, the RNA was first deadenylated using RNase H and oligod(T)+ Figure 5B shows that without deadenylation, longer fragments are produced from the cDNA of the mutants (lanes 3, 5, and 6 compared to 2 and 4)+ In particular, in Adh nBR114 and Adh n4, it is apparent that products of up to 100 nt longer are amplified (indicated by a double arrow)+ In the mutant Adh BR112 , the length of the fragments is also increased but to a much smaller extent (this is more obvious in Fig+ 5C, compare lane 6 with lane 7)+ Here the fragments are about 10-20 nt longer+…”
Section: Transcripts Carrying Premature Termination Codons Have Longementioning
confidence: 99%
See 1 more Smart Citation
“…Deadenylation is considered the first step in the degradation of ARE-containing mRNAs (11,38,44). To find out if activation of the p38/MK2 pathway imposes changes in this process, the poly(A) tail of ␤-globin mRNA containing the IL-8 ARE, isolated from cells cotransfected with MKK6 2E or empty vector, was analyzed by polyacrylamide gel electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…The exact requirements for p38/MK2-induced stabilization in terms of both cis-acting sequences and trans-acting factors have not yet been defined. mRNA decay begins with loss of the poly(A) tail (deadenylation), and the AREs were observed to enhance deadenylation (11,38,44). More recently, AREs have been suggested to mediate the recruitment of the exosome, a complex of RNases involved in 3Ј-to-5Ј degradation of the mRNA body (8,30).…”
mentioning
confidence: 99%